An Analysis of The Variables Influencing Job Satisfaction Among Volunteers In Non Profit Organizations - Yakin, Ikram (Equator Journal of Management and Entrepreneurship (EJME), 2026)
Non-profit organizations are highly dependent on the sustainability of volunteer engagement, making volunteer job satisfaction a key factor in maintaining the effectiveness and sustainability of the organization. This study aims to analyze the influence of organizational culture, communication, and transformational leadership on volunteer job satisfaction in non-profit organizations. The research population includes all volunteers working in non-profit institutions, such as social foundations and non-governmental organizations in West Kalimantan, Indonesia, with an unknown population size. Sampling was conducted using purposive sampling with a total of 148 volunteers as respondents. This study used a quantitative approach with a survey method, where data were collected through a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that organizational culture and communication had a positive and significant effect on volunteer job satisfaction. Transformational leadership was also found to have a positive and significant effect, and had the most dominant influence compared to other variables. These findings confirm that transformational leadership plays a strategic role in increasing volunteer job satisfaction in non-profit organizations. The contribution of this study lies in strengthening empirical research on human resource management in the non-profit sector, particularly in the context of volunteers, as well as providing practical implications for non-profit organization managers to develop transformational leadership, a supportive organizational culture, and effective communication.